The Effect of Monetary Policy Instruments and Macroeconomic Indicators on the Jakarta Composite Index (JCI): An Empirical Study in Indonesia - Talbani Farlian; Nur Aidar; Cheny Seftarita; Meutia Handayani; Rollis Juliansyah; M. Asrar Farabi (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study examines the effects of monetary policy variables and macroeconomic conditions on Indonesia’s stock market performance, as represented by the Jakarta Composite Index (JCI), over the period January 2010 to December 2024. Specifically, the study examines the influence of the BI interest rate, inflation, and the rupiah exchange rate on the JCI. Using secondary time-series data obtained from Bank Indonesia and the Indonesia Stock Exchange, the study applies the Ordinary Least Squares (OLS) method to estimate the relationship among the variables. The empirical results show that the BI interest rate has a negative and statistically significant effect on the JCI, indicating that an increase in interest rates tends to reduce stock market performance by discouraging investment activity. The rupiah exchange rate is found to have a positive and statistically significant effect on the JCI, suggesting that exchange rate movements are an important determinant of stock market fluctuations during the observed period. Meanwhile, inflation does not have a statistically significant effect on the JCI, implying that changes in inflation did not directly influence stock market performance over the sample period. Overall, the findings confirm that interest rate policy and exchange rate dynamics play a more prominent role than inflation in shaping the movement of Indonesia’s stock market. These results provide important implications for investors and policymakers in understanding the macroeconomic factors affecting the JCI.